De l’hétérodoxie à l’orthodoxie : les espaces religieux de George Keith - Louisiane Ferlier (Revue Française de Civilisation Britannique)
Not unlike G. K. Chesterton, George Keith (1639-1716)’s conversions allow us in this paper to demonstrate how fluid the concept of ‘orthodoxy’ was in the English-speaking world. A Quaker thinker and writer, the Scot converted to Quakerism after the Restoration, at a time when Scotland was divided by the conflict between Presbyterians and Episcopalians. He justified this choice by defining religious revelation as a ‘spiritual travel’. This paper examines his own tormented spiritual travel, showing the superposition of his religious mobility (from Quakerism to Anglicanism) to his geographical mobility (from Britain to the American colonies and back), to which is added his intellectual mobility, which brought him into the circles of influential thinkers such as William Penn, Henry More or Gilbert Burnet. Keith, a marginal figure, therefore exemplifies the complexity of the British world which underwent, at the turn of the seventeenth century, a spatial redefinition due to its expansion in the New World and a reshaping of its religious landscape from the centre to the margins.